Characterization of primary osteocyte-like cells from rat mandibles - Zakhary, I (Oral Surg Oral Med Oral Pathol Oral Radiol, 2016)
OBJECTIVE: The mandible is continuously undergoing remodeling due to mechanobiological factors, such as chewing forces, tooth loss, orthodontic forces, and periodontitis. The effects of mechanical stress and biological signals in bone homeostasis have been the focus of many investigations. However, much of this research utilized osteocytes derived from long bones while little is known about the mandible-derived osteocytes. This study tests a protocol to isolate and grow osteocytes from rat mandible. DESIGN: Rat mandibles were harvested, sectioned into small pieces and subjected to a sequence chemical treatment and enzymatic digestion. The treated tissues were cultured for a few weeks while cells emerged. Cells were sorted by using the osteocyte marker podoplanin, an early marker for osteocyte differentiation. The cells were then characterized according to morphology, biochemical markers (osteocalcin, podoplanin, and sclerostin) and alkaline phosphatase activity and compared to an isotype cell line MLO-Y4 cells. RESULTS: The mandibular osteocytic-cells had stellate shape and were positive for osteocalcin, podoplanin and sclerostin and low alkaline phosphatase activity compared to MLO-Y4 osteocyte-like cells. CONCLUSIONS: The protocol to isolate osteocyte-like cells will allow the investigators to investigate the mechanobiological differences in biomechanical response between these mandibular and long-bone osteocyte-like cells under various conditions.